KORELASI KEGIATAN APRESIASI SENI TARI DENGAN KREATIVITAS SISWA KELAS IV DI SDN 16 LANDAU SILING - Idha, Arya; Mastiah, Mastiah; Mukhlisin, Mukhlisin (Bestari: Jurnal Pendidikan dan Kebudayaan, 2025)
Abstract : This study aims to determine the relationship between dance appreciation activities and the creativity of fourth grade students of SDN 16 Landau Siling. This study uses a quantitative method, namely to determine the closeness of the relationship between dance appreciation activities and the creativity of fourth grade students of SDN 16 Landau Siling. the form of this research is a correlation study in which there are variables (x) namely dance appreciation activities with variables (y) namely student creativity, there is a relationship that influences each other or reciprocally between the two variables.The sample and population in this study were all fourth grade students of SDN 16 Landau Siling totaling 20 students with the number of male students totaling 8 people and the number of female students totaling 12 people. After being analyzed, it is known that there is a positive and significant relationship between dance art appreciation activities and student creativity. This is shown from the results of the hypothesis test stating that both have a significant relationship because with the provision of sig. 0.01 <0.05, there is a relationship between variable X and variable Y. And with the provision of 34282.783> 2.10092, it can be concluded that there is a significant relationship between variable X and variable Y. Based on the calculation results, it can be concluded that there is a positive and significant relationship between Dance Art Appreciation Activities and the Creativity of Class IV Students of SDN 16 Landau Siling. Keywords: Dance Art Appreciation Activities, Student Creativity. Abtsrak: Penelitian ini bertujuan untuk mengetahui hubungan kegiatan apresiasi seni tari dengan kreativitas siswa kelas IV SDN 16 Landau Siling. Penelitian ini menggunakan metode kuantitatif yaitu untuk mengetahui keeratan hubungan antara kegiatan apresiasi seni tari dengan kreativitas siswa kelas IV SDN 16 Landau Siling. bentuk penelitian ini adalah studi korelasi yang di dalamnya terdapat variabel (x) yaitu kegiatan apresiasi seni tari dengan variabel (y) yaitu kreativitas ssiswa terdapat hubungan yang saling mempengaruhi atau timbal balik di antara kedua variabel tersebut.Sampel dan populasi dalam penelitian ini adalah seluruh siswa kelas IV SDN 16 Landau Siling yang berjumlah 20 siswa dengan jumlah siswa laki-laki berjumlah 8 orang dan jumlah siswa perempuan berjumlah 12 orang. Setelah dianalisis diketahui bahwa terdapat hubungan yang positif dan signifikan antara kegiatan apresiasi seni tari dan kreativitas siswa. Hal ini ditunjukkan dari hasil uji hipotesis menyatakan bahwa keduanya memiliki hubungan yang signifikan karena dengan ketentuan sig. 0,01< 0,05 maka terdapat hubungan variabel X dengan variabel Y. dan dengan ketentuan 34282.783 > 2.10092 maka dapat di simpulkan bahwa terdapat hubungan yang signifikan terhadap variabel X dengan variabel Y. Berdasarkan hasil perhitungan dapat disimpulkan bahwa terdapat hubungan yang positif dan signifikan antara kegiatan apresiasi seni tari dengan kreativitas siswa kelas IV SDN 16 Landau Siling. Kata Kunci : Kegiatan Apresiasi Seni Tari, Kreativitas Siswa.